The Relationship between Work-family Conflict, Burnout Dimensions and Intention to Leave among Female Nurses - A Farhadi; Y Movahedi; M Nalchi; M Daraei; R Mohammadzadegan (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: It is a long time that human science researchers, especially industrial and organizational experts have noticed the importance of work-family conflict as a substantive and essential foundation for proficiency of organizational processes and job satisfaction. The aim of this study was determining the relationship between work - family conflict with job burnout and intention to leave among female nurses working in university hospitals of Khorramabad.   Material and Methods: It was a descriptive correlational study . The study population consisted of all female nurses working in university hospitals of Khorramabad city . The sample (n=220) was recruited by stratified random sampling method. Data was collected by Netemeyer (1996) Work-Family Conflict questionnaire, Maslach & Jackson (1981) burnout questionnaire and Kamant et al., (1979) turnover questionnaire and analyzed by descriptive statistics , and correlation coefficient Pearson and regression analysis using SPSS-PC (v. 19) .   Results: There was a significant positive relationship between work-family conflict and burnout (P<0/01). There was also a direct relationship between work-family conflict and burnout dimensions ( emotional exhaustion, depersonalization, and personal accomplishment) (P<0/01) . Work-family conflict could also predict intention to leave among these female nurses (P<0/01).   Conclusion: Regarding the findings, more assessments and continuous interventions to prevent job burnout and turnover in nurses is necessary .   Received: 10 Jul 2013   Accepted: 11 Oct 2013